FTEM framework (AIS, 2021)
The AIS has developed the Foundations, Talent, Elite and Mastery framework to capture different sporting pathways. FTEM provides a practical tool to assist sporting stakeholders (National Sporting Organisations (NSOs) and their personnel, coaches, teachers, parents etc.) in reviewing, planning and supporting athlete pathways. The framework consists of four macro phases of athlete development (Foundation, Talent, Elite and Mastery), which are further differentiated into 10 micro phases.